Two Argan Oil Phytosterols, Schottenol and Spinasterol, Attenuate Oxidative Stress and Restore LPS-Dysregulated Peroxisomal Functions in Acox1−/− and Wild-Type BV-2 Microglial Cells - Soukaina Essadek; Catherine Gondcaille; Stéphane Savary; Mohammad Samadi; Joseph Vamecq; Gérard Lizard; Riad El Kebbaj; Norbert Latruffe; Alexandre Benani; Boubker Nasser; Mustapha Cherkaoui-Malki; Pierre Andreoletti (MDPI AG, 2023)
Oxidative stress and inflammation are the key players in neuroinflammation, in which microglia dysfunction plays a central role. Previous studies suggest that argan oil attenuates oxidative stress, inflammation, and peroxisome dysfunction in mouse brains. In this study, we explored the effects of two major argan oil (AO) phytosterols, Schottenol (Schot) and Spinasterol (Spina), on oxidative stress, inflammation, and peroxisomal dysfunction in two murine microglial BV-2 cell lines, wild-ype (Wt) and Acyl-CoA oxidase 1 (Acox1)-deficient cells challenged with LPS treatment. Herein, we used an MTT test to reveal no cytotoxicity for both phytosterols with concentrations up to 5 µM. In the LPS-activated microglial cells, cotreatment with each of these phytosterols caused a significant decrease in intracellular ROS production and the NO level released in the culture medium. Additionally, Schot and Spina were able to attenuate the LPS-dependent strong induction of Il-1β and Tnf-α mRNA levels, as well as the iNos gene and protein expression in both Wt and Acox1−/− microglial cells. On the other hand, LPS treatment impacted both the peroxisomal antioxidant capacity and the fatty acid oxidation pathway. However, both Schot and Spina treatments enhanced ACOX1 activity in the Wt BV-2 cells and normalized the catalase activity in both Wt and Acox1−/− microglial cells. These data suggest that Schot and Spina can protect cells from oxidative stress and inflammation and their harmful consequences for peroxisomal functions and the homeostasis of microglial cells. Collectively, our work provides a compelling argument for the protective mechanisms of two major argan oil phytosterols against LPS-induced brain neuroinflammation.